Perkembangan Nilai Tukar Sejalan Dengan Kebijakan Negara - Nandang Ihwanudin; Dena Febriani (ISLAMICA, 2022)
In making payments using money as a medium of exchange, public economic transactions. Certain countries have different types and names of currencies in their payment instruments. The affects the value in different currencies in a country. Likewise, Indonesia uses the rupiah currency; Bath is the official currency in Thailand, the US dollar in the United States, and the ringgit are the official currencies in Malaysia. In the case of international trade-related to other countries, the open economic cycle is buying and selling goods/services between residents. Different payment instruments or types of currency in a country are certain things that need to consider in the value equation or currency. The price for currency exchange determines the similarity in value and currency, namely the exchange rate for foreign currency exchange with domestic currency. The exchange rate is related to a country's monetary international economic policy. The exchange rate affects the wheels of the country's economic progress. Exchange rate stability in the economic reform policy has become one of the state policies. Determination of the state in exchange rate renewal by assessing the economic development of another country is an analysis of the relationship between exchange rate changes in a country.